Membrane guanylate cyclase, a multimodal transduction machine: history, present, and future directions - Sharma, Rameshwar K.; Duda, Teresa (Frontiers in Molecular Neuroscience, 2014)
A sequel to these authors' earlier comprehensive reviews which covered the field of mammalian membrane guanylate cyclase (MGC) from its origin to the year 2010, this article contains 13 sections. The first is historical and covers MGC from the year 1963–1987, summarizing its colorful developmental stages from its passionate pursuit to its consolidation. The second deals with the establishment of its biochemical identity. MGC becomes the transducer of a hormonal signal and founder of the peptide hormone receptor family, and creates the notion that hormone signal transduction is its sole physiological function. The third defines its expansion. The discovery of ROS-GC subfamily is made and it links ROS-GC with the physiology of phototransduction. Sections ROS-GC, a Ca2+-Modulated Two Component Transduction System to Migration Patterns and Translations of the GCAP Signals Into Production of Cyclic GMP are Different cover its biochemistry and physiology. The noteworthy events are that augmented by GCAPs, ROS-GC proves to be a transducer of the free Ca2+ signals generated within neurons; ROS-GC becomes a two-component transduction system and establishes itself as a source of cyclic GMP, the second messenger of phototransduction. Section ROS-GC1 Gene Linked Retinal Dystrophies demonstrates how this knowledge begins to be translated into the diagnosis and providing the molecular definition of retinal dystrophies. Section Controlled By Low and High Levels of [Ca2+]i, ROS-GC1 is a Bimodal Transduction Switch discusses a striking property of ROS-GC where it becomes a “[Ca2+]i bimodal switch” and transcends its signaling role in other neural processes. In this course, discovery of the first CD-GCAP (Ca2+-dependent guanylate cyclase activator), the S100B protein, is made. It extends the role of the ROS-GC transduction system beyond the phototransduction to the signaling processes in the synapse region between photoreceptor and cone ON-bipolar cells; in section Ca2+-Modulated Neurocalcin δ ROS-GC1 Transduction System Exists in the Inner Plexiform Layer (IPL) of the Retinal Neurons, discovery of another CD-GCAP, NCδ, is made and its linkage with signaling of the inner plexiform layer neurons is established. Section ROS-GC Linkage With Other Than Vision-Linked Neurons discusses linkage of the ROS-GC transduction system with other sensory transduction processes: Pineal gland, Olfaction and Gustation. In the next, section Evolution of a General Ca2+-Interlocked ROS-GC Signal Transduction Concept in Sensory and Sensory-Linked Neurons, a theoretical concept is proposed where “Ca2+-interlocked ROS-GC signal transduction” machinery becomes a common signaling component of the sensory and sensory-linked neurons. Closure to the review is brought by the conclusion and future directions.